Structure-guided discovery and characterization of novel FLT3 inhibitors for acute myeloid leukemia treatment - Budha, Bishal; Basu Choudhury, Gourab; Hossain, Md. Shohag; Acharya, Arjun (PLOS ONE, 2025)
FLT3 (FMS-like tyrosine kinase 3), a receptor tyrosine kinase, is frequently mutated in acute myeloid leukemia (AML), a hematologic malignancy marked by aggressive proliferation, poor prognosis, and high relapse rates. Although FDA-approved FLT3 inhibitors exist, their clinical efficacy is often undermined by resistance and off-target effects, underscoring the critical necessity for more effective and selective agents. Here, we employed a structure-based computational approach combining pharmacophore screening via Pharmit and the MolPort compound library to identify novel FLT3 inhibitors. Pharmacophore modeling, virtual screening, and docking identified two promising leads, MolPort-002-705-878 and MolPort-007-550-904, with binding affinities of –11.33 and –10.66 kcal/mol, correspondingly. These compounds were further evaluated using molecular dynamics (MD) simulations to assess binding stability, density functional theory (DFT) calculations to explore electronic reactivity, and ADMET profiling to examine pharmacokinetic and toxicity parameters. MD results, including principal component analysis (PCA) and free energy landscape (FEL) mapping, supported the integrity of the FLT3–lead complexes, with MM/GBSA binding free energies (ΔG) of –39.23 kcal/mol and –27.03 kcal/mol for MolPort-002-705-878 and MolPort-007-550-904, respectively. DFT analysis indicated favorable frontier molecular orbital energies and reactivity indices, characterized by a low HOMO–LUMO energy gap and a reactive dipole moment. ADMET predictions indicated acceptable drug-likeness and low toxicity, pending further experimental confirmation. This integrated in silico pipeline highlights the therapeutic potential of these molecules as next-generation FLT3 inhibitors and offers a scalable strategy for targeted AML therapeutics.